Pengaruh Pembelajaran Project Based Learning dengan integrasi ChatGPT terhadap Peningkatan Hasil Belajar Sosiologi Siswa - Walidaroyani, Ainia; Pawestri, Dilahing (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze the effect of Project Based Learning (PjBL) with the help of ChatGPT on student learning outcomes in Sociology subjects. ChatGPT as artificial intelligence technology provides support in the form of interactive explanations, project completion assistance, and learning resources that can be accessed at any time by students. The research method used was quasi-experiment with pretest-posttest control group design. The research sample consisted of 60 11th grade high school students who were divided into two groups, namely the experimental group using PjBL assisted by ChatGPT and the control group using conventional learning methods. The research instrument was a multiple choice test to measure learning outcomes before and after treatment. The results showed a significant increase in posttest scores in the experimental group compared to the control group. The t-test analysis showed a significant difference (p < 0.05) between the two groups, indicating that the integration of ChatGPT in PjBL learning effectively improved students' sociology learning outcomes. This finding underscores the importance of utilizing AI technology to support active learning models and improve learning quality. This study recommends the application of similar technologies in other learning contexts as well as further research to examine the long-term impact of using AI in education.